2016
DOI: 10.1371/journal.pone.0150737
|View full text |Cite
|
Sign up to set email alerts
|

Readmission for Acute Exacerbation within 30 Days of Discharge Is Associated with a Subsequent Progressive Increase in Mortality Risk in COPD Patients: A Long-Term Observational Study

Abstract: Background and ObjectiveTwenty per cent of chronic obstructive pulmonary disease (COPD) patients are readmitted for acute exacerbation (AECOPD) within 30 days of discharge. The prognostic significance of early readmission is not fully understood. The objective of our study was to estimate the mortality risk associated with readmission for acute exacerbation within 30 days of discharge in COPD patients.MethodsThe cohort (n = 378) was divided into patients readmitted (n = 68) and not readmitted (n = 310) within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 23 publications
11
67
0
1
Order By: Relevance
“…The most important prognostic factor was exacerbation-related hospitalisation. In particular, readmission within 30 days after COPD exacerbation was correlated with an increased risk of mortality [28]. The most important predictor of frequent exacerbations is a history of exacerbations [29].…”
Section: Prior Exacerbationsmentioning
confidence: 99%
“…The most important prognostic factor was exacerbation-related hospitalisation. In particular, readmission within 30 days after COPD exacerbation was correlated with an increased risk of mortality [28]. The most important predictor of frequent exacerbations is a history of exacerbations [29].…”
Section: Prior Exacerbationsmentioning
confidence: 99%
“…It was stated that COPD patients with low pulmonary functions and poor dyspnea scores returned to hospital within 30 days after hospital discharge (23). In another study, dyspnea was considered to be a significant risk factor for hospital revisits (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of post-discharge mortality, early hospital readmission for a new event of AECOPD (for example, in a period within 30 days from discharge) is a variable that "per se" influences prognosis of patients. Although several variables have been found to be predictors of early readmission [20][21][22] , in fact, is has been demonstrated that readmission of patients to hospital in this period have a higher subsequent and progressive risk of death until in long follow-up period of 3-year [23] . Starting from the concept that a predictor of a 30-day readmission is the variable ≥ 2 previous exacerbation in a period of 1-year prior to index hospitalization (Hazard Ratio-HR = 2.47, 95% CI 1.51-4.05, p < 0.001) [23] , the relationship in the events of AECOPD between the past and the prognosis is very close.…”
Section: Introductionmentioning
confidence: 97%
“…Although several variables have been found to be predictors of early readmission [20][21][22] , in fact, is has been demonstrated that readmission of patients to hospital in this period have a higher subsequent and progressive risk of death until in long follow-up period of 3-year [23] . Starting from the concept that a predictor of a 30-day readmission is the variable ≥ 2 previous exacerbation in a period of 1-year prior to index hospitalization (Hazard Ratio-HR = 2.47, 95% CI 1.51-4.05, p < 0.001) [23] , the relationship in the events of AECOPD between the past and the prognosis is very close. Moreover, a study published in 2012 reported the presence of at least one previous exacerbation of COPD in the previous year [OR = 3.9, 95% CI 1.6-9.9, p = 0.004)] [19] as an independent predictor of adverse outcome defined by death during hospitalisation or the 1-month follow-up.…”
Section: Introductionmentioning
confidence: 97%